2021
DOI: 10.3390/su13073935
|View full text |Cite
|
Sign up to set email alerts
|

Big Data-Based Assessment of Political Risk along the Belt and Road

Abstract: Political risk assessment has become increasingly important in recent years, especially with the launch of the Belt and Road Initiative (BRI) and with Covid-19 still ravaging the world. This study aims to assess systematically the political risk of BRI countries during the period from 2013 to 2019 based on three big data sets, the Global Database of Events, Language, and Tone (GDELT), China Global Investment Tracker (CGIT), and Armed Conflict Location & Event Data Project (ACLED). It is found that to prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…The data platform is widely used as an important data analysis tool. Moreover, it is scientific and reliable to take the Baidu index as a statistical analysis tool in the era of big data (Sun et al, 2021;Yaacob et al, 2021). Therefore, the search indexes on the Baidu index platform are selected here as the OPA data.…”
Section: Analysis Methods and Data Source Of Spatial And Temporal Cha...mentioning
confidence: 99%
“…The data platform is widely used as an important data analysis tool. Moreover, it is scientific and reliable to take the Baidu index as a statistical analysis tool in the era of big data (Sun et al, 2021;Yaacob et al, 2021). Therefore, the search indexes on the Baidu index platform are selected here as the OPA data.…”
Section: Analysis Methods and Data Source Of Spatial And Temporal Cha...mentioning
confidence: 99%
“…Sun et al found a strong positive correlation between political risk and China's total investments. They confirmed that it would be necessary for China to invest in B&R countries with low or even negligible political risks [15]. Duan et al have put forward a fuzzy integrated evaluation model for energy investment risk based on entropy weight, conducting an integrated assessment of the energy investment risk of B&R countries.…”
Section: Literature Review 121 Research On China's Ofdi Location Choi...mentioning
confidence: 96%
“…With the continuous advancement of the BRI, academic circles have conducted extensive discussions on issues related to investment between China and B&R countries [3,6,8], and the location choice has been a hot issue for numerous scholars [4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. At present, the research on the location choice of China's OFDI in B&R countries can be roughly divided into two aspects.…”
Section: Literature Review 121 Research On China's Ofdi Location Choi...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of its geographic structure, this research was able to quickly absorb and integrate massive geographic data, including the WHO. [71,79,81,82,85,87]…”
Section: Accuracy Of Datamentioning
confidence: 99%